O trabalho de professoras com deficiência visual: uma análise político-social da inclusão profissional na rede regular de ensino de belo horizonte. - Naim Rodrigues de Araújo (2020)
We aim to broaden the discussions on the inclusion of people in handicap situation in the work market from the contributions of two teachers of the city of Belo Horizonte in handicap situation related to the optical system. In addition, we chose to look in the literature, not only about work inclusion, but especially about the marginalizing history of people in handicap situation in Brazil, which allows us to broaden our understanding of the reflexes still perceived today. In addition to the literature review, the methodological option was to conduct a participant observation with the teachers, semi-structured interview and topical life story. As a result, we observed that labor inclusion is gradually being implemented, however, there is a discrepancy between the public and private sectors. In the case of a teacher in handicap situation, it is necessary to admit a new socio cultural subject in the teacher / student relationship: the teacher support assistant. Gradually, it seems, the participation of teachers in handicap situation increases the notion of inclusion in students, who tend to become more inclusive and develop "prossocial behavior” - willingness to help others.